The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s1806-92902015000900004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymer-coated slow-release urea on performance, ruminal fermentation, and blood metabolites in dairy cows

Abstract: -The objective of this experiment was to quantify the effects of feeding polymer-coated slow-release urea on nutrient intake and total tract digestion, milk yield and composition, nutrient balances, ruminal fermentation, microbial protein synthesis, and blood parameters in dairy cows. Sixteen Holstein cows (580±20 kg of live weight (mean ± standard deviation); 90 to 180 days in milk (DIM); and 28 kg/d of average milk yield) were used in a replicated 4 × 4 Latin square experimental design. The animals were assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
4
13
1
1
Order By: Relevance
“…Miranda et al (2019) reported that there were no differences in most of the blood parameters when cows were fed various urea sources. Similar results were observed by Calomeni et al (2015), who recorded no differences in blood parameters when SBM was replaced partially with protein sources such as yeastderived microbial protein or SRU.…”
Section: Resultssupporting
confidence: 84%
“…Miranda et al (2019) reported that there were no differences in most of the blood parameters when cows were fed various urea sources. Similar results were observed by Calomeni et al (2015), who recorded no differences in blood parameters when SBM was replaced partially with protein sources such as yeastderived microbial protein or SRU.…”
Section: Resultssupporting
confidence: 84%
“…Nevertheless, we did not detect differences on microbial protein synthesis agreeing with [28] who reported no differences in purine derivatives production of Nellore steers fed the urea sources of the current study. In addition, Calomeni et al [9] found no differences in DM intake, apparent digestibility and microbial protein synthesis of dairy cows fed the same polymer-coated SRA as used in this study or feed grade urea, but the authors added 0.9 g/kg DM of the commercial products.…”
Section: Discussionmentioning
confidence: 66%
“…These effects are related to the fact that several cellulolytic bacteria use N from ammonia to grow in rumen [7]. However, other studies have reported no effects of replacing feed grade urea by SRU on ruminal fermentation [8], nutrient digestibility and N excretion [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Starea, biuret and complexes of urea with formaldehyde or molasses have been used in the rumen to avoid ammonia‐N toxicity; yet slow release rates have failed to improve N utilization in in vitro trials . Other commercial products based on urea used to reduce the degradation of N in the rumen are Rumapro® and Optigen®; the ruminal degradation rate of these products is comparable to vegetable protein concentrates .…”
Section: Introductionmentioning
confidence: 99%